PENGARUH KUALITAS PELAYANAN DAN CITRA PERUSAHAAN TERHADAP LOYALITAS PELANGGAN INDIHOME PT. TELKOM INDONESIA DI BANDA ACEH DENGAN KEPUASAN DAN KEPERCAYAAN PELANGGAN SEBAGAI VARIABEL MEDIASI - Abdul Muzammil; Mukhlis Yunus; Nurdasila Darsono (Jurnal Manajemen Inovasi, 2017)
ABSTRACT The aim of this study was to determine the influence of service quality and corporate image on customer satisfaction, customer trust and customer loyalty as well as to determine the role of customer satisfaction and customer trust on mediating the influence of service quality and corporate image on customer loyalty. This study was conducted on 270 customer IndiHome PT. Telkom Indonesia in Banda Aceh. The sample data were statistically analyzed using confirmatory factor analysis (CFA) and structural equation modeling (SEM). The result show that both service quality and corporate image have a significantly direct effect on customer satisfaction, customer trust and customer loyalty. And then this study also found the role of customer satisfaction and customer trust are indirectly mediate the influence of service quality and corporate image on customer loyalty either by simple mediation or multiple mediation. Keywords: Customer Loyalty, Customer Satisfaction, Customer Trust, Service Quality, Corporate Image